INFLUENCE OF HYBRID AND WEATHER CONDITIONS ON YIELD, PROTEIN AND OIL CONTENTS IN GRAIN OF MAIZE - Dorina BONEA; Ioana Claudia DUNĂREANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Considering the role of maize in both animal feed and human consumption, improving the quality of maize grain should be investigated with the same perseverance as the grain yield. The main objectives proposed in this research were to evaluate the influence of the hybrid, weather conditions and their interaction on the yield, protein and oil contents in grain maize, and to investigate the relationships between these traits. Field experiments were performed for two consecutive years at ARDS Șimnic. The results obtained showed that the weather conditions during the study years were the determinant factor of variability in grain yield (88%), and the hybrid was the determinant factor of variability in protein and oil contents (84% and 83%, respectively). In average, in 2018, a significantly higher grain yield (9.05 t/ha) and a significantly lower oil content (4.2%) were registered compared to 2019 (6.08 t/ha and 4.5%, respectively), while the protein content was almost similar in both years (12.5% and 12.3%, respectively). The hybrids P 9903 (7.88 t/ha) and DK 5068 (7.79 t/ha) obtained the highest average grain yields. The hybrid F 376 had the lowest average grain yield (7.03 t/ha) but the highest average protein content (13.4%) and oil content (5.3%). Negative correlations between traits suggested that an increase in the grain yield meant a decrease in the grain quality traits (protein and oil contents).